2001
DOI: 10.2981/wlb.2001.006
|View full text |Cite
|
Sign up to set email alerts
|

The diet of the brown bearUrsus arctosin the Pasvik Valley, northeastern Norway

Abstract: The seasonal composition of and the annual variation in the diet of the brown bear Ursus arctos in the Pasvik Valley, northeastern Norway, were estimated based on the analysis of 137 bear scats. The importance of moose Alces alces and reindeer Rangifer tarandus in the diet was given special attention, because results from Russia suggest that brown bears are generally more carnivorous in the north. Ungulates, especially adult moose, comprised the most important food item for bears in the Pasvik Valley during sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 22 publications
(51 reference statements)
4
86
1
1
Order By: Relevance
“…This supports previous findings that the majority of autumn fat reserves come from carbohydrates from berries (Welch et al 1997). We found that berries constituted 68% of the estimated dietary energy content in autumn, which was intermediate between the 49% reported from northeastern Norway, ca 1100 km north-northeast of our study area (Persson et al 2001) and the 80-81% documented from Jämtland, Sweden, ca 300 km northwest of our study area (Dahle et al 1998).…”
Section: Use Of Berries According To Their Occurrence During Hyperphagiasupporting
confidence: 87%
See 2 more Smart Citations
“…This supports previous findings that the majority of autumn fat reserves come from carbohydrates from berries (Welch et al 1997). We found that berries constituted 68% of the estimated dietary energy content in autumn, which was intermediate between the 49% reported from northeastern Norway, ca 1100 km north-northeast of our study area (Persson et al 2001) and the 80-81% documented from Jämtland, Sweden, ca 300 km northwest of our study area (Dahle et al 1998).…”
Section: Use Of Berries According To Their Occurrence During Hyperphagiasupporting
confidence: 87%
“…In the European boreal forest ecosystems, brown bears commonly consume vegetable matter, insects, and ungulates, with the importance of vertebrate meat increasing with latitude (Vulla et al 2009). Studies of brown bear diet, based on scat studies or foraging sign, have been conducted in four areas of Scandinavia, (Haglund 1966, Elgmork and Kaasa 1992, Dahle et al 1998, Swenson et al 1999, Persson et al 2001), but have not described the annual variation in diet or food resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sizeable presence of herbaceous plants in the early summer of 1978, and from spring to early summer of 1998-2000, corroborates earlier studies of Hokkaido brown bears (Aoi 1985;Ohdachi and Aoi 1987;Yamanaka and Aoi 1988;Sato 2002) and those of other regions of the world (Cicnjak et al 1987;Mattson et al 1991;Clevenger et al 1992;Elgmork and Kaasa 1992;McLellan and Hovey 1995;Persson et al 2001).…”
Section: Comparison Of Dietssupporting
confidence: 77%
“…The diet of grizzly bears has been studied for over two decades in many areas in North America and Europe, and is known to comprise seasonally abundant, nutrient-rich food (Hamer et al 1991;Craighead et al 1995;Dahle et al 1998;Persson et al 2001;Nielsen et al 2003;Munro et al 2006). Generally, their diet is highly diverse both temporally and spatially, as is the case for most habitat generalists or omnivores.…”
Section: Introductionmentioning
confidence: 99%